The effect of OK-432 (Picibanil) injection on the histopathology of nasal turbinate. Issue 12 (12th October 2015) - Sengul, S; Kaygusuz, İ; Akin, M M; Yalcin, Ş; Karlidag, T; Keles, E; Arslan, İ
Abstract: Objective: This study aimed to assess the histopathological effect of OK-432 (Picibanil) on rabbit nasal turbinates. Methods: A total of 21 rabbits were divided into 3 treatment groups and various parts of both nasal turbinates were injected with 0.5 ml OK-432, 0.2 ml OK-432 or 0.6 ml saline (control). Bilateral nasal turbinates were later excised and studied under light microscopy to assess any histopathological changes. Results: Animals in the 0.2 ml and 0.5 ml OK-432 groups exhibited mild ciliary loss, goblet cell loss and epithelial damage, and a marked increase in inflammatory cell infiltration, submucosal vascularisation and fibrosis. There was a significant difference in histopathological changes between the two OK-432 treated groups. In addition, each OK-432 treated group had significantly more inflammatory cell infiltration, increased submucosal vascularisation and fibrosis compared with controls. Conclusion: The marked fibrosis observed in OK-432-injected turbinates may be responsible for a reduction in turbinate size.